Importance of strategy formation and management to achieve a competitive advantage at manufacturing SMEs in India - Sand, Vinit (2017)
This assignment deals with the presence of strategic and managerial effectiveness within the Indian manufacturing SMEs. The SME sectors in India play an inevitable role in raising the GDP and the employment status of the country. It provides employment to a large number of individuals irrespective of their education, skills and expertise. The labor section of the SMEs is provided with on-job training system in the organizations, which help them in conducting their work. The greater dependency on the agricultural sector reduces the economic status and financial position of the individuals. This assignment also discusses that strategies and management are required in the SMEs as it helps in systematic and methodical operation within the organization. Several challenges that SMEs face in India are also discussed. Along with the government's involvement in reducing the challenges of these SMEs are also discussed in this context. I have taken 112 employees and laborers for quantitative analysis and 5 managers for qualitative analysis. Various research ethics and limitations that I had to adhere to are also discussed. Finally, recommendations to the challenges faced by the Indian SMEs in the country are also discussed.